Teaching literacy to learners with dyslexia a multisensory approach - Kelly, Kathleen S.; Phillips, Sylvia (SAGE, 2016)
The second edition of this bestselling book provides a structured multi-sensory programme for teaching literacy to children and young people from 5-18 with dyslexia and other specific literacy difficulties. Supported by a wealth of resources available online and updated throughout, the new edition now includes a brand new section on Implementing the Accelerated Programme for learners who have already acquired some literacy skills. This includes: A placement test to indicate whether the programme is appropriate ; A diagnostic assessment procedure to determine where the learner should begin on the Accelerated Programme ; Examples of lesson plans, reading cards and spelling cards to help teachers prepare resources for their students. With tried and tested strategies and activities this book continues to provide everything you need to help improve and develop the literacy skills of learners in your setting including: the rationale for a structured multi-sensory approach ; the development of phonological, reading, writing and spelling skills ; working with learners who have English as an Additional Language (EAL) ; lesson structure and lesson-planning ; alphabet and dictionary skills ; memory work and study skills ; teaching the programme to groups ; ideas for working with young children. -- Provided by publisher.